2013
DOI: 10.1016/j.pnpbp.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effect of α-tocopherol in a mouse model of depressive-like behavior induced by TNF-α

Abstract: Taking into account that pro-inflammatory cytokines and oxidative and nitrosative stress are implicated in the pathogenesis of depression and that α-tocopherol has antidepressant, anti-inflammatory and antioxidant properties, this study investigated the ability of α-tocopherol to abolish the depressive-like behavior induced by i.c.v. administration of TNF-α in the mouse TST. Additionally, we investigated the occurrence of changes in the levels of Bcl2 and Bax and phosphorylation of GSK-3β (Ser9) in the hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 118 publications
2
30
0
Order By: Relevance
“…These findings corroborate with the behavioral results presented here and with previous studies from our group that showed the reversal effect of ALA on the depressivelike behavior of animals treated with CORT (Silva et al, , 2014. Furthermore, several studies show that antioxidants are able to reverse depressive-like behavior alone or in association with antidepressants (Lobato et al, 2010;Moretti et al, 2012;Mazloom et al, 2013;Manosso et al, 2013;Amr et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…These findings corroborate with the behavioral results presented here and with previous studies from our group that showed the reversal effect of ALA on the depressivelike behavior of animals treated with CORT (Silva et al, , 2014. Furthermore, several studies show that antioxidants are able to reverse depressive-like behavior alone or in association with antidepressants (Lobato et al, 2010;Moretti et al, 2012;Mazloom et al, 2013;Manosso et al, 2013;Amr et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…In general, minocycline and cytokine antagonists are effective to block inflammation-induced depression when administered before immune stimulation. The same effect is obtained with a wide variety of anti-inflammatory or anti-oxidant natural compounds, such as curcumin, apigenine, honkiol, xiaobuxin-tang flavonoid extract, perillaldehyde, ginseng saponins, and alpha-tocopherol (Wang et al 2014; Li et al 2015a; Sulakhiya et al 2014; An et al 2015; Ji et al 2014; Kang et al 2011; Manosso et al 2013). However, it is not known whether the anti-inflammatory treatment can block behavioral signs of depression once they have developed.…”
Section: Targeting Inflammation-induced Depression: Translational Aspmentioning
confidence: 71%
“…Antidepressive and antioxidative effects of ascorbic acid have also been reported after a unpredictable chronic mild stress protocol (232). Antidepressant properties have been described for other antioxidants as well (201,211,247,278,285). A randomized, double-blind, placebo-controlled pilot study in humans showed that the addition of vitamin C to antidepressant therapy significantly improved clinical outcomes (10).…”
Section: Indicators Of Oxidative Imbalancementioning
confidence: 98%